A β-glucosidase hyper-production Trichoderma reesei mutant reveals a potential role of cel3D in cellulase production. Issue 1 (December 2016) - Li, Chengcheng; Lin, Fengming; Li, Yizhen; Wei, Wei; Wang, Hongyin; Qin, Lei; Zhou, Zhihua; Li, Bingzhi; Wu, Fugen; Chen, Zhan
Abstract Background The conversion of cellulose by cellulase to fermentable sugars for biomass-based products such as cellulosic biofuels, biobased fine chemicals and medicines is an environment-friendly and sustainable process, making wastes profitable and bringing economic benefits.Trichoderma reesei is the well-known major workhorse for cellulase production in industry, but the low β-glucosidase activity inT. reesei cellulase leads to inefficiency in biomass degradation and limits its industrial application. Thus, there are ongoing interests in research to develop methods to overcome this insufficiency. Moreover, although β-glucosidases have been demonstrated to influence cellulase production and participate in the regulation of cellulase production, the underlying mechanism remains unclear. Results TheT. reesei recombinant strain TRB1 was constructed fromT. reesei RUT-C30 by the T-DNA-based mutagenesis. Compared to RUT-C30, TRB1 displays a significant enhancement of extracellular β-glucosidase (BGL1) activity with 17-fold increase, a moderate increase of both the endoglucanase (EG) activity and the exoglucanase (CBH) activity, a minor improvement of the total filter paper activity, and a faster cellulase induction. This superiority of TRB1 over RUT-C30 is independent on carbon sources and improves the saccharification ability of TRB1 cellulase on pretreated corn stover. Furthermore, TRB1 shows better resistance to carbon catabolite repression than RUT-C30. Secretome characterization of TRB1 shows that the amount of CBH, EG and BGL in the supernatant ofT. reesei TRB1 was indeed increased along with the enhanced activities of these three enzymes. Surprisingly, qRT-PCR and gene cloning showed that in TRB1 β-glucosidase cel3D was mutated through the random insertion by AMT and was not expressed. Conclusions TheT. reesei recombinant strain TRB1 constructed in this study is more desirable for industrial application than the parental strain RUT-C30, showing extracellular β-glucosidase hyper production, high cellulase production within a shorter time and a better resistance to carbon catabolite repression. Disruption of β-glucosidase cel3D in TRB1 was identified, which might contribute to the superiority of TRB1 over RUT-C30 and might play a role in the cellulase production. These results laid a foundation for future investigations to further improve cellulase enzymatic efficiency and reduce cost forT. reesei cellulase production.